Toward a Macaque Model of HIV-1 Infection: Roadblocks, Progress, and Future Strategies - Thippeshappa, Rajesh; Kimata, Jason T.; Kaushal, Deepak (Frontiers in Microbiology, 2020)
The human-specific tropism of Human Immunodeficiency Virus Type 1 (HIV-1) has complicated the development of a macaque model of HIV-1 infection/AIDS that is suitable for preclinical evaluation of vaccines and novel treatment strategies. Several innate retroviral restriction factors, such as APOBEC3 family of proteins, TRIM5α, Tetherin, and SAMHD1, that prevent HIV-1 replication have been identified in macaque cells. Accessory proteins expressed by Simian Immunodeficiency virus (SIV) such as viral infectivity factor (Vif), viral protein X (Vpx), viral protein R (Vpr) and negative factor (Nef) have been shown to play key roles in overcoming these restriction factors in macaque cells. Thus, substituting HIV-1 accessory genes with those from SIV may enable HIV-1 to replication in macaques. We and others have constructed macaque-tropic HIV-1 derivatives (also called simian-tropic HIV-1 (stHIV-1) or Human-Simian Immunodeficiency virus (HSIV)) carrying SIV vif to overcome APOBEC3 family proteins. Additional modifications to HIV-1 gag in some of the macaque-tropic HIV-1 have also been done to overcome TRIM5α restriction in rhesus and cynomolgus macaques. Although these viruses replicate persistently in macaque species, they do not result in CD4 depletion. Thus, these studies suggest that additional blocks to HIV-1 replication exist in macaques that prevent high-level viral replication. Furthermore, serial animal-to-animal passaging of macaque-tropic HIV-1 in vivo has not resulted in pathogenic variants that cause AIDS in immunocompetent macaques. In this review, we discuss recent developments made towards developing macaque model of HIV-1 infection.